2016
DOI: 10.1038/srep39200
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the cytoplasmic incompatibility-inducing Wolbachia strain wMel in an important agricultural pest insect

Abstract: The wMel Wolbachia strain was known for cytoplasmic incompatibility (CI)-induction and blocking the transmission of dengue. However, it is unknown whether it can establish and induce CI in a non-dipteran host insect. Here we artificially transferred wMel from Drosophila melanogaster into the whitefly Bemisia tabaci. Fluorescence in situ hybridisation demonstrated that wMel had successfully transfected the new host. Reciprocal crossing was conducted with wMel-transfected and wild-type isofemale lines, indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 52 publications
0
15
1
Order By: Relevance
“…Increasing the number of compatible and incompatible crosses would be needed to decide whether the lack of statistical significance in the data presented here is due to the lack of a biological effect or due to the effect being just weak; for technical reasons, additional crosses are impractical at the point of writing this manuscript. In contrast to our results, Wolbachia w Mel, once transinfected into other hosts, induced a high level of incompatibility, such as in Drosophila simulans (Poinsot, Bourtzis, Markakis, Savakis, & Merçot, 1998), in the whitefly Bemisia tabaci (Zhou & Li, 2016) and in the mosquito Aedes aegypti (Hoffmann, Iturbe‐Ormaetxe, et al, 2014; Hoffmann, Coy, Gibbard, & Pelz‐Stelinski, 2014; Walker et al, 2011) (Table 1).…”
Section: Discussioncontrasting
confidence: 99%
“…Increasing the number of compatible and incompatible crosses would be needed to decide whether the lack of statistical significance in the data presented here is due to the lack of a biological effect or due to the effect being just weak; for technical reasons, additional crosses are impractical at the point of writing this manuscript. In contrast to our results, Wolbachia w Mel, once transinfected into other hosts, induced a high level of incompatibility, such as in Drosophila simulans (Poinsot, Bourtzis, Markakis, Savakis, & Merçot, 1998), in the whitefly Bemisia tabaci (Zhou & Li, 2016) and in the mosquito Aedes aegypti (Hoffmann, Iturbe‐Ormaetxe, et al, 2014; Hoffmann, Coy, Gibbard, & Pelz‐Stelinski, 2014; Walker et al, 2011) (Table 1).…”
Section: Discussioncontrasting
confidence: 99%
“…5). The absolute quantification method was used, in which wsp copy number amplified from experimental samples is compared against known concentrations of a plasmid standard [56, 6367].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Wolbachia are maternally transmitted and have evolved several strategies to manipulate host reproduction including parthenogenesis, feminization, male killing and cytoplasmic incompatibility to facilitate their own proliferation and transmission (Weeks & Breeuwer, 2001;Zheng et al, 2011a;Beckmann et al, 2017;LePage et al, 2017;Miyata et al, 2017;Harumoto et al, 2018). In the last decade, several lines of evidence have suggested that Wolbachia can be used as environmentally friendly biocontrol agents to control insect pest populations and disease vectors (McMeniman et al, 2009;Hoffmann et al, 2011;Moreira et al, 2011;Nguyen et al, 2015;Zhou & Li, 2016;Aliota et al, 2016aAliota et al, , 2016bGarcia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%